2016
DOI: 10.1590/s1518-8787.2016050006307
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior in Brazilian children and adolescents: a systematic review

Abstract: OBJECTIVE To describe the methodological characteristics of the studies selected and assess variables associated with sedentary behavior in Brazilian children and adolescents.METHODS For this systematic review, we searched four electronic databases: PubMed, Web of Knowledge, LILACS, SciELO. Also, electronic searches were applied in Google Scholar. A supplementary search was conducted in the references lists of the included articles and in non-indexed journals. We included observational studies with children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
2
34

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 65 publications
6
57
2
34
Order By: Relevance
“…Corroborating our results, recent literature systematic review study showed that most of the studies analyzed found association between sedentary behavior and increased body weight levels in children and adolescents 28 . One of the main limitations of this work was the construction of screen time variable from self-reported information, which may have underestimated this sedentary behavior.…”
Section: Discussionsupporting
confidence: 88%
“…Corroborating our results, recent literature systematic review study showed that most of the studies analyzed found association between sedentary behavior and increased body weight levels in children and adolescents 28 . One of the main limitations of this work was the construction of screen time variable from self-reported information, which may have underestimated this sedentary behavior.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, data from urban and rural communities in the Portuguese Midlands comprising 100 boys and 115 girls aged 13-14 year-old found 3.34 ± 1.79 h/day and 2.63±1.39 h/day of ST, respectively 41 . Recently, a systematic review described the methodological characteristics and assessed variables associated with SB among Brazilian children and adolescents and identified a great number of cross-sectional studies around the country 42 . Besides a global matrix comparing 15 countries suggest that SB in general are better in low-income countries 9 , we found high ST values (Girls: 3.36 ± 1.83; Boys: 4.2 ± 2.28 h/day; p<0.05) and prevalence of ST ≥2 h/day (Girls: 81.0%; Boys: 76.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Em outro estudo realizado na cidade de Pelotas (RS) com escolares de 10 a 12 anos de idade, o comportamento sedentário apresentou associação com o ambiente escolar, com maior prevalência de acordo com a diminuição da participação dos escolares em aulas de Educação Física curriculares 35 . Sabe-se que o ambiente escolar é propício para a redução com comportamento sedentário 23 , porém o presente estudo não encontrou resultados significativos envolvendo a aula de educação física. Este dado instiga a discussão acerca da prática de atividade física em atividades com e sem organização estrutural, como por exemplo, o recreio escolar.…”
Section: Discussionunclassified